2016
DOI: 10.1503/cmaj.150708
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in older adults in long-term care facilities

Abstract: Clinical and laboratory assessment is needed to establish a diagnosis of urinary tract infectionThere are several approaches to diagnosing urinary tract infection in older adults, with certain common elements in diagnostic criteria. The accepted criteria are two clinical symptoms (from the following list: temperature > 38°C, urinary urgency or frequency, acute dysuria, hypogastric pain, costovertebral angle tenderness) and laboratory findings of bacteriuria (> 100 000 colony-forming units/mL) or pyuria (> 10 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…Age wise the study population was between the age of 8 and 85 Elderly individuals appear to be more susceptible to T2D. The maximum number of T2D patients was found within age group 41-60 years 17 (65.4%), T2DM patients age mean (54.4±10.1) , which in line with a local study by Mansour et al (2020), that reported the mean age of type II diabetics being (51.4±3 years).The results seem to disagree with a study by Ajayi and Radhakrishnan (2016) in, the most common age group inflected with UTI is above 60 years of age rather than meddle aged population which the current study presents. While the maximum number of T1D patients was found within age group ≤20years 10 (50%).And, the age mean and standard deviation of T1DM (26.3±8.9 years), that in line with previous study by Goldberg et al (2020) which concluded that the T1DM prevalence at a younger age (21.2±3 years).…”
Section: Figure (1)contrasting
confidence: 54%
“…Age wise the study population was between the age of 8 and 85 Elderly individuals appear to be more susceptible to T2D. The maximum number of T2D patients was found within age group 41-60 years 17 (65.4%), T2DM patients age mean (54.4±10.1) , which in line with a local study by Mansour et al (2020), that reported the mean age of type II diabetics being (51.4±3 years).The results seem to disagree with a study by Ajayi and Radhakrishnan (2016) in, the most common age group inflected with UTI is above 60 years of age rather than meddle aged population which the current study presents. While the maximum number of T1D patients was found within age group ≤20years 10 (50%).And, the age mean and standard deviation of T1DM (26.3±8.9 years), that in line with previous study by Goldberg et al (2020) which concluded that the T1DM prevalence at a younger age (21.2±3 years).…”
Section: Figure (1)contrasting
confidence: 54%
“…Another reason is the contamination rate in our study, which concerns one out of two positive samples (53.41%; n =1758), which constitutes a considerable diagnostic loss. Finally, clinical evaluation is often limited by the difficulty of obtaining a reliable history from patients who are often unable to communicate their symptoms adequately 12 , 20 23 . Differentiating urinary tract infection and asymptomatic bacteriuria can be a challenge in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating urinary tract infection and asymptomatic bacteriuria can be a challenge in older adults. Diagnosis of UTI must be based on a thorough clinical evaluation, presence of new genitourinary signs and symptoms, and the exclusion of other possible diagnoses 12 , 20 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common indication is for a UTI (17,18). Overdiagnosis and treatment of UTI in long-term care is well recognized, with at least half of antibiotic prescriptions for this indication considered unnecessary (19).…”
Section: Urinary Tract Infection In Long-term Care Homesmentioning
confidence: 99%